Soybean LEAFY COTYLEDON 1: A Key Target for Genetic Enhancement of Oil Biosynthesis - Sehrish Manan; Khulood Fahad Alabbosh; Abeer Al-Andal; Waqas Ahmad; Khalid Ali Khan; Jian Zhao (Agronomy, 2023)
Soybean is an important oilseed crop that is used as a feed for livestock and has several industrial uses. Lipid biosynthesis and accumulation primarily occur during seed development in plants. This process is regulated by several transcription factors and interconnected biochemical pathways. This study investigated the role of glycine max LEAFY COTYLEDON 1 (GmLEC1) in soybean seed development and the accumulation of storage reserves. The overexpression of GmLEC1 significantly increased the amount of triacylglycerol (TAG) in transgenic Arabidopsis seeds compared to the wild-type and an atlec1 mutant. Similarly, the high expression of GmLEC1 led to a 12% increase in TAG content in transgenic soybean hairy roots compared to the control. GmLEC1 also altered the fatty acid composition in transgenic Arabidopsis seeds and soybean hairy roots. Additionally, the overexpression of GmLEC1 resulted in a reduction in starch accumulation in seeds and vegetative tissues, as well as changes in cotyledon and seed morphology. The cotyledons of the atlec1 mutant displayed abnormal trichome development, and the seeds were smaller and less tolerant to desiccation. A complementation assay in Arabidopsis restored normal cotyledon phenotype and seed size. The main downstream targets of LEC1 are GL2 and WRI1, which were found to participate in fatty acid biosynthesis and trichome formation through the regulation of phytohormones and various transcription factors involved in seed development and maturation. The findings of this study suggest that GmLEC1 controls seed development and regulates the accumulation of seed storage compounds. Furthermore, these results demonstrate that GmLEC1 could be a reliable target for the genetic improvement of oil biosynthesis in soybean.